Multiplex identification of drug‐resistant Gram‐positive pathogens using stuffer‐free MLPA system. Issue 23 (27th September 2016) - Chung, Boram; Park, Chulmin; Cho, Sung‐Yeon; Shin, Sun; Yim, Seon‐Hee; Jung, Gyoo Yeol; Lee, Dong‐Gun; Chung, Yeun‐Jun
Abstract : Early detection of pathogens from blood and identification of their drug resistance are essential for sepsis management. However, conventional culture‐based methods require relatively longer time to identify drug‐resistant pathogens, which delays therapeutic decisions. For precise multiplex detection of drug‐resistant Gram‐positive pathogens, we developed a method by using stuffer‐free multiplex ligation‐dependent probe amplification (MLPA) coupled with high‐resolution CE single‐strand conformation polymorphisms (CE‐SSCP) system. We designed three probe sets for genes specific to Gram‐positive species ( Staphylococcus aureus : nuc, Enterococcus faecium : sodA, and Streptococcus pneumoniae : lytA ) and two sets for genes associated with drug resistance ( mecA and vanA ) to discriminate major Gram‐positive pathogens with the resistance. A total of 94 different strains (34 reference strains and 60 clinical isolates) were used to validate this method and strain‐specific peaks were successfully observed for all the strains. To improve sensitivity of the method, a target‐specific preamplification step was introduced and, consequently, the sensitivity increased from 10 pg to 100 fg. We also reduced a total assay time to 8 h by optimizing hybridization time without compromising test sensitivity. Taken together, our multiplex detection system can improve detection of drug‐resistant Gram‐positive pathogens from sepsis patients' blood.